TRAINING FOR FISH BASED FOOD PROCESSING IN CREATING ECONOMIC OPPORTUNITIES FOR RESIDENTS IN TARUNA JAYA DISTRICT - Nurhasanah Nurhasanah; A. Hadian Pratama Hamzah; Prabawa Eka Soesanta; Suratni Suratni (Universitas Pahlawan Tuanku Tambusai, 2023)
Segara Jaya Village, Taruma Jaya District, Bekasi Regency has a mangrove ecotourism location which is now starting to be visited by tourists. The location is more specifically used as the Bekasi Regency Mangrove Restoration and Learning Center by the Ministry of Maritime Affairs and Fisheries. Even though many tourists have visited there, the life of the people is still not up to standard. Based on preliminary observations, it is known that people's income is between Rp. 800,000 to Rp. 900,000. This amount is far from enough to meet their daily needs. The people in Segara Jaya Village generally rely on their livelihood as fishermen. The life of fishermen in this village is still very simple. In order to help meet the needs of the family, the fishermen's wives in Segara Jaya Village joined the Joint Business Group (KUB) which is engaged in the business of processing catches whose results are sold to tourists who visit the mangrove ecotourism there. In community service activities the approach taken is training and mentoring methods in marketing. As for the results of this community service activity, the results were obtained, the participants were able to practice it with good results, how to process tuna into processed food in the form of dumplings and tekwan. The drawback in this activity is that the processed products have a fishy taste that is very thin so that they tend to be unusual, further training is expected for new findings related to processing methods by suppressing the thick smell of fish and seasoning according to certain doses in the process of making this type of food.